1928
DOI: 10.1002/jlac.19284670114
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über einige Heterocyclen und deren Tautomeriefähigkeit

Abstract: P r o m m und K a p e l l e r -A d l e r ,Salmiak, nicht, wie irrtiimlich angenommen wurde, ein Substitutionsvorgang, sondern es erfolgt eine Additionsreaktion unter Bildung des Chlorhydrats einer Base, die zungchst als das 2-p-Diamido-5-cblormethyloxazolidin aufgcfa6t wurde. F r o m m , F a n t l und Fisch') gelang es zu beweisen, da6 Oxazolinringe durch Einwirkung von Salmiak aufgesprengt werden , wobei Stoffe mit offener Kette, Guanidinoalkobole, entstehen. Somif ware die Reaktionsgleichung fur Chlormethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1932
1932
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Bleaching (V) (VI) (IV) (VII) Table 1 shows the herbicidal activity of 3-substitutedphenylimino-5, 6-dihydro -6, 6-dimethyl-3H-thiazolo[2, 3-c] [1,2,4]thiadiazoles against A. retroflexus. Among mono-substituted Table 1 Structures, physical properties and herbicidal activities of 3-(substituted)phenylimino -5, 6-dihydro-6, 6-dimethyl-3H-thiazolo[2, 3-c] [1, 2, 41thiadiazoles. compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), 4-chloro derivative (3) showed a moderate activity. and 4-trifluoromethoxy (7) also showed weak activities, while other 4-substituted compounds were inactive.…”
Section: Herbicidal Activitymentioning
confidence: 99%
“…Bleaching (V) (VI) (IV) (VII) Table 1 shows the herbicidal activity of 3-substitutedphenylimino-5, 6-dihydro -6, 6-dimethyl-3H-thiazolo[2, 3-c] [1,2,4]thiadiazoles against A. retroflexus. Among mono-substituted Table 1 Structures, physical properties and herbicidal activities of 3-(substituted)phenylimino -5, 6-dihydro-6, 6-dimethyl-3H-thiazolo[2, 3-c] [1, 2, 41thiadiazoles. compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), 4-chloro derivative (3) showed a moderate activity. and 4-trifluoromethoxy (7) also showed weak activities, while other 4-substituted compounds were inactive.…”
Section: Herbicidal Activitymentioning
confidence: 99%
“…This has led to a search for a convenient method of synthesizing previously unknown 2-amino-5-hydroxymethyl-2-thiazolines with alkyl, benzyl, alkylbenzyl, dibenzyl, and hetaryl substituents in the amino group. The literature bears isolated items of information on the synthesis of such compounds from the corresponding 5-haloderivatives of thiazoline in the presence of silver salts [4,5], but unfortunately they lack descriptions of the experimental methods and proof of the structures of the substances.We have examined the hydrolysis of the hydrohalides of 2-amino-substituted 5-halomethyl-2-thiazolines 1a-h made by traditional methods: iodination of the corresponding N'-derivatives of N-allylthiourea or reaction of N-(2,3-dibromopropyl)isothiocyanate with amines [6][7][8].Previous studies have shown that isomeric six-membered rings (thiazines) are formed in these reactions as well as thiazolines [9, 10]. However, these reactions are usually performed in polar media with heating, and from the reaction mixtures one isolates only five-membered thiazoline rings, because under these conditions there is an easy dihydrothiazine-thiazoline rearrangement [11].…”
mentioning
confidence: 99%
“…This has led to a search for a convenient method of synthesizing previously unknown 2-amino-5-hydroxymethyl-2-thiazolines with alkyl, benzyl, alkylbenzyl, dibenzyl, and hetaryl substituents in the amino group. The literature bears isolated items of information on the synthesis of such compounds from the corresponding 5-haloderivatives of thiazoline in the presence of silver salts [4,5], but unfortunately they lack descriptions of the experimental methods and proof of the structures of the substances.…”
mentioning
confidence: 99%
“…, F (I 10 -III 10 ), CI (I 11 -III 11 ), Br (I 3,12 -III 3 , 12 ),NO 2 (I 4,13 -III 4 aqueous KOH [10] or sodium methylate [11] did not lead to the formation of 5-methylthiazole derivatives. The initial thiazoline was produced.…”
mentioning
confidence: 99%